Compliance monitoring via a Bluetooth‐enabled retainer: A prospective clinical pilot study. (10th May 2019) - Castle, Eric; Chung, Philip; Behfar, Mohammad H.; Chen, Matthew; Gao, Jonathan; Chiu, Nicholas; Nelson, Gerald; Roy, Shuvo; Oberoi, Snehlata
Structured Abstract: Objectives: To conduct a prospective pilot trial to test the clinical efficacy and accuracy of a newly developed Bluetooth‐enabled retainer, which was synchronized with an iOS mobile application, cloud database and provider webpage. Setting and Sample Population: Five orthodontic residents in a university setting. Material and Methods: At the delivery of the retainers (T0), each participant was given an Bluetooth‐enabled retainer, logbook and iPod Touch installed with the mobile application. Participants were instructed to wear the retainer for 12 hours per day and record in the logbook each time the retainer was inserted or removed and trained to synchronize the device daily to the mobile application. After the 5‐day study period (T1), statistical analysis was performed comparing the device‐reported data to the logbook data using two calculation methods. Results: From T0 – T1, the participants wore their retainers for a median of 11.55 hours per day and the median difference between the self‐reported (logbook) data and the device data was 35 minutes or 5.1% over the 5‐day study period. Using an adjusted method to calculate the device‐reported wear time, the median error was 13 minutes or 1.9%. Conclusion: Subjects were able to successfully wear the retainer and upload the data to the mobile application and cloud database. Patient compliance and technical issues could be monitored daily via the provider webpage, and early intervention was possible with reminder messaging. The Bluetooth‐enabled retainer showed a clinically acceptable level of accuracy and usability that validates it for future clinical testing.